The practical Einstein : experiments, patents, inventions - Illy, József, 1933- (Johns Hopkins University Press, 2012)
"Albert Einstein may be best known as the wire-haired whacky physicist who gave us the theory of relativity, but that's just one facet of this genius's contribution to human knowledge and modern science. As József Illy expertly shows in this book, Einstein had an eminently practical side as well. As a youth, Einstein was an inveterate tinkerer in the electrical supply factory his father and uncle owned and operated. His first paid job was as a patent examiner. Later in life, Einstein contributed to many inventions, including refrigerators, microphones, and instruments for aviation. In published papers, Einstein often provided ways to test his theories and fundamental problems of the scientific community of his times. He delved deeply into a variety of technological innovations, most notably the gyrocompass, and consulted for industry in patent cases and on other legal matters. Einstein also provided explanations for common and mundane phenomena, such as the meandering of rivers. In these and other hands-on examples culled from the Einstein Papers, Illy demonstrates how Einstein enjoyed leaving the abstract world of theories to wrestle with the problems of everyday life. While we may like the idea of Einstein as a genius besotted by extra dimensions and too out-of-this world to wear socks, The Practical Einstein gives ample evidence that not only is this characterization incomplete, it is also an unfair representation of a man who sought to explore the intricacies of nature, whether in theory or practice."--Project Muse.